Architectural glass to resist seismic and extreme climatic events - Behr, Richard A. (Boca Raton, Fla. : CRC Press ; Oxford : Woodhead, 2009)
"Architectural Glass to Resist Seismic and Extreme Climatic Events will be an essential resource for architects, structural, civil and architectural engineers, researchers and those involved in designing and specifying building glazing and cladding materials in areas where severe windstorms, snow and earthquakes are a threat."--BOOK JACKET.
1. Building code seismic requirements for architectural glass : the United States / R. E. Bachman and S. M. Dowty -- 2. Glazing and curtain wall systems to resist earthquakes / A. M. Memari and T. A. Schwartz -- 3. Snow loads on building envelopes and glazing systems / R. Flood -- 4. Architectural glass to resist snow loads / R. H. Davies and N. Vigener -- 5. Wind pressures on building envelopes / K. C. Mehta -- 6. Architectural glass to resist wind pressures / C. Barry -- 7. Architectural glass to resist wind-borne debris impacts / D. B. Hattis -- 8. Glazing systems to resist windstorms on special buildings / J. E. Minor -- 9. Test methods for performance of glazing systems and exterior walls during earthquakes and extreme climatic events / S. A. Warner.
Includes bibliographical references and index.
Keywords: Glass construction